Stress-strain state analysis of a fastening device for an arched long good on a ﬂatcar - S. A. Petrachkou; M. G. Gegedesh (Вестник Научно-исследовательского института железнодорожного транспорта, 2025)
Introduction. The need to improve the ways of placing and securing goods on rolling stock is determined by the constant expansion of the range of goods transported, an increase in the maximum speeds of freight trains, as well as the development and implementation of new railway cars designs in the transportation process. New designs of devices for arched loads, including long goods, are proposed. At the same time, the methods of analysing freight handling and cargo fastening schemes adopted in the practice of transportation do not allow to conclude about the reliability of such non-standard devices and their retaining properties.Materials and methods. A study of the stress-strain state of a fastening device for an arched long good on a rolling stock is performed. The loads acting on the device in the longitudinal and transverse directions are determined analytically.Results. The values of normal, equivalent (according to Mises) stresses and deformations of the developed structure under adverse conditions of its loading are obtained.Discussion and conclusion. The results of the calculations obtained on the basis of ﬁnite element analysis made it possible to develop recommendations for the application of the proposed design to arched long goods to eliminate tipping and translational movements in the longitudinal and transverse directions.